Are Adult ADHD Patients Good Informants of Their Symptoms? A Qualitative Literature Review of Concordance Between Clinician and Self-Report ADHD Symptoms. Issue 9 (September 2018) - Abrams, Jessica; Faraone, Stephen V.; Woodworth, K. Yvonne; Spencer, Thomas J.; Biederman, Itai; Biederman, Joseph
Abstract : Abstract: To conduct a comprehensive review on the agreement between clinician-rated and self-reported attention-deficit/hyperactivity disorder (ADHD) symptoms in adults, the following terms were searched in PubMed: "ADHD self-concordance, " "Self-report AND ADHD AND Valid, " "(self-report) AND ADHD AND clinician, " and "(self-report) AND ADHD AND versus AND investigator." Nine articles met our inclusion and exclusion criteria (English language, operationalized measures of clinician-rated and self-reported ADHD, and neither a review nor opinion article). Among the clinical studies, correlation coefficients were on average 0.69 for the total ADHD symptoms score. The epidemiological studies had an average kappa statistic of 0.58 for ADHD diagnoses. The studies of adult relatives of youth with ADHD had an average correlation coefficient of 0.74 for the ADHD total symptoms score. Our review supports the informativeness of self-reported assessments of ADHD symptoms, which has important implications for management and monitoring of ADHD.